School bullying and learning in high school students - Bravo-Cedeño, Janina Alexandra; Avila-Rosales, Francisca Margarita (International research journal of management, IT and social sciences, 2022)
The research was based on the study of bullying school and its impact on the learning of the students of the Educational Unit June 5 #34, of the Canuto parish, of the Chone canton. According to initial inquiries and diagnostic tests, it was possible to identify peer violence as one of the problems that significantly affects the performance of schoolchildren. From this, relevant themes were established in the theoretical framework in relation to school bullying and learning, which allowed analyzing the causes and consequences of bullying in the teaching-learning process. The objective was to determine the level of bullying and its effects on children’s learning. The research had a mixed approach, that is, qualitative and quantitative, of a documentary type, with the implementation of the deductive method and the application of the survey as a data collection technique to investigate the behavior of the students and the intervention processes by of teachers in cases of school violence. It was obtained as a result that school bullying has a negative impact on student learning, due to psychological conditions, so it is necessary that teachers and parents are prepared to deal with these situations.